Afviklingen af de middelalderlige klostre i Danmark og Nordtyskland - Kristensen, Hans Krongaard (Kuml, 2021)
The dissolution and subsequent fate of Medieval monasteries in Denmark and northern Germany There are certain differences in the building histories of monasteries in Denmark and northern Germany due to economic and political developments in the two areas during the Middle Ages. The monasteries in Denmark were founded over a very long period, although none were established in the 14th century and many in the 15th century. In northern Germany, due to the late conversion, establishment took place over a shorter period, with extensive building activity in the 13th and 14th centuries. The major building boom seen in Denmark up to the Reformation is not evident in the north of Germany. In the case of the Cistercian abbeys in Denmark, it is characteristic that very few of their churches ever acquired the planned length, and their cloisters were rarely completed until a late date. This contrasts sharply with the situation in northern Germany. The nunneries in both areas lack systematic investigation. In Denmark, the nuns had, in many cases, an earlier church for their services, so it is uncertain what they themselves preferred. Whatever the situation, we can see that the nuns had their choir on a pulpit at the western end of the nave. It is also quite clear in Denmark that the main wing containing the dormitory was placed to the west. Some scholars in Germany believe that the nuns had their main wing to the east, like the monks. The mendicant friaries in Denmark are best known from excavations, whereas in the large towns of northern Germany these still stand or are known from 19th century drawings. Very little is known about the early, closed friaries in the smaller towns. The friaries in the major Hanseatic towns had larger churches than those in Denmark and often also two cloisters. It is quite clear from the examples of monastery dissolution that their fate at the Reformation was, to a major degree, dependent primarily on the faith of the ruler – i.e. a city council, a duke or a king – and secondly on the power this ruler had to carry out their wishes. Accordingly, we see a different pattern in relation to the Reformation in the various principalities and towns of northern Germany. Interestingly, the Lutheran Reformation in northern Germany did not progress from west to east as is the expected norm for ideas, but rather from east to west. In East Prussia, the Reformation was introduced in 1525, jointly and without difficulties by the new duke, the Teutonic Order, the two bishops and the other clergy. Danzig underwent a Lutheran reformation in 1525, but due to a political change in the city council, the king of Poland had an opportunity to intervene and reverse the changes. The religious reformation in Danzig was consequently delayed by 30 years. The Reformation in Stralsund became rather violent in 1525 but ended after a few days in a common agreement, giving consent to the Lutheran faith. The town was many years ahead of the remainder of the Duchy of Pomeranian. In Hamburg, the citizens and the town council decided, after some debate, to adopt the Lutheran faith in 1528. A similar, uncomplicated transition took place in Rostock in 1531 and Wismar in 1532, too. In other towns, like Lübeck and Lüneburg, there were major divisions between the town council and ordinary citizens, leading to a drawn-out process, but these towns became Protestant nevertheless in 1530-31. The Reformation that came into force in all Pomerania was decided at a meeting, Landtag, in Treptow in 1534. That is slightly earlier than in Denmark and was without the support of the nobility. In Mecklenburg, with a divided government, there was a long period of transition, during which both faiths existed at the same time. It was first in 1549 that all Mecklenburg was declared a Protestant country with support from all the Estates. The political situation in Denmark was clearly different from that in Mecklenburg and Pomerania. The government in Denmark was in a way more centralised. On the other hand, the king was very much dependent on his council (Rigsrådet) with a strong component of Catholic clergy. The banishing of the mendicant orders from the friaries was clearly accepted by King Frederik I and was undertaken over a short period (1528-32). However, legal suppression of the friars did not happen until 1537, when the new king, Christian III, was victorious in the civil war. There was therefore a long period when the situation was unresolved and the Reformation in Denmark was a quite extended and in some cases rather violent process. The final Reformation came much later than in most of the neighbouring states in northern Germany. Many of the monastic buildings (or more correctly friaries) were offered to the towns in which they stood, but most disappeared either at the Reformation or during subsequent centuries. In Mecklenburg-Vorpommern, many friaries were abolished swiftly at the Reformation, which took place at rather different times. In the larger towns, they were then reused as schools and hospitals. On the other hand, it seems that the preserved examples are better known than those in Denmark, while in Farther Pomerania most have been lost over time. As for the landowning monasteries in rural areas, there are few well-preserved examples in either Denmark or northern Germany. But as a result of excavations and other investigations, we have supplementary information for many existing monastic churches and buildings. Due to the way in which the Reformation was undertaken, it seems that the nunneries are best preserved in Mecklenburg and Pomerania, where many continued as a Protestant Damenstift, while more survives of the male monasteries in Denmark. As for the physical remains of the monasteries in Mecklenburg-Vorpommern and in Medieval Denmark, there are now not many completely preserved Medieval monasteries, almost 500 years after the Reformation; there are even fewer in Farther Pomerania. But all in all, and looking across borders, we have, however, a great deal of information on the layout of Medieval monasteries in northern Europe – far better than in many Catholic areas with Baroque modernisations.